Enigmatic role of auxin response factors in plant growth and stress tolerance - Liu, Ling; Yahaya, Baba Salifu; Li, Jing; Wu, Fengkai (Frontiers in Plant Science, 2024)
Abiotic and biotic stresses globally constrain plant growth and impede the optimization of crop productivity. The phytohormone auxin is involved in nearly every aspect of plant development. Auxin acts as a chemical messenger that influences gene expression through a short nuclear pathway, mediated by a family of specific DNA-binding transcription factors known as Auxin Response Factors (ARFs). ARFs thus act as effectors of auxin response and translate chemical signals into the regulation of auxin responsive genes. Since the initial discovery of the first ARF in Arabidopsis, advancements in genetics, biochemistry, genomics, and structural biology have facilitated the development of models elucidating ARF action and their contributions to generating specific auxin responses. Yet, significant gaps persist in our understanding of ARF transcription factors despite these endeavors. Unraveling the functional roles of ARFs in regulating stress response, alongside elucidating their genetic and molecular mechanisms, is still in its nascent phase. Here, we review recent research outcomes on ARFs, detailing their involvement in regulating leaf, flower, and root organogenesis and development, as well as stress responses and their corresponding regulatory mechanisms: including gene expression patterns, functional characterization, transcriptional, post-transcriptional and post- translational regulation across diverse stress conditions. Furthermore, we delineate unresolved questions and forthcoming challenges in ARF research.